Ice phenomena as a tourism asset on the southern coast of the Baltic Sea - Girjatowicz, Józef (Turyzm/Tourism, 2015)
The aim of the paper is to present selected ice phenomena occurring on the waters of the southern coast of the Baltic Sea which may be of tourism value. On the basis of his own observations and research over the period 2002-11, the author analysed interesting ice phenomena documented in 20 photographs showing in the main ice forms (grease ice ridges, ice hummocks, thrust ice). The photographs present the sea (8), lagoons (7) and lakes (5). The author has included brief descriptions of selected ice phenomena, focusing on interesting forms and their origins, which may encourage potential tourists to observe and explore icecovered water bodies. Ice tourism could be a part of cognitive, environmental, specialist, hiking, winter, seasonal or even occasional tourism.